Efficacy and Safety of Bilastine in the Treatment of Allergic Rhinitis: A Systematic Review and Meta-analysis - Singh Randhawa, Aranjit; Mohd Noor, Norhayati; Md Daud, Mohd Khairi; Abdullah, Baharudin (Frontiers in Pharmacology, 2022)
Bilastine is a non-sedating second generation H1 oral antihistamine (OAH) for treating allergic rhinitis (AR) patients. The effect of bilastine has not previously been evaluated in a meta-analysis. The aim of this review was to determine the efficacy and safety of bilastine in treating AR. An electronic literature search was performed using Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Science Direct and Google Scholar up to March 2021. Randomized controlled trials comparing bilastine with placebo and standard pharmacotherapy were included. The included studies must have diagnosis of AR established by clinicians and the outcomes must have a minimum of two weeks of follow-up period. The primary outcomes assessed were total symptom score (TSS), nasal symptom score (NSS) and non-nasal symptom score (NNSS). The secondary outcomes were discomfort due to rhinitis, quality of life (QOL) and adverse events. The risk of bias and quality of evidence for all studies were appraised. The meta-analysis was done using Review Manager 5.3 software based on the random-effects model. The search identified 135 records after removal of duplicates. Following screening and review of the records, fifteen full-text articles were assessed for eligibility. Five trials involving 3,329 patients met the inclusion criteria. Bilastine was superior to placebo in improving TSS, NSS, NNSS, rhinitis discomfort score and QOL but has comparable efficacy with other OAHs in TSS, NSS, NNS, rhinitis discomfort score and QOL. There was no difference in adverse effects when bilastine was compared against placebo and other OAHs except for somnolence. Bilastine has fewer incidence of somnolence compared to cetirizine. The overall quality of evidence ranged from moderate to high quality. Bilastine is effective and safe in treating the overall symptoms of AR with comparable efficacy and safety with other OAHs except somnolence. Whilst bilastine has similar efficacy to cetirizine, somnolence is notably less in bilastine.